2023
DOI: 10.1097/iop.0000000000002552
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating ChatGPT on Orbital and Oculofacial Disorders: Accuracy and Readability Insights

Michael Balas,
Ana Janic,
Patrick Daigle
et al.

Abstract: Purpose: To assess the accuracy and readability of responses generated by the artificial intelligence model, ChatGPT (version 4.0), to questions related to 10 essential domains of orbital and oculofacial disease. Methods: A set of 100 questions related to the diagnosis, treatment, and interpretation of orbital and oculofacial diseases was posed to ChatGPT 4.0. Responses were evaluated by a panel of 7 experts based on appropriateness and accuracy, with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…[9] It was also shown that ChatGPT performs accurately when responding to questions about orbital and oculofacial disorders, with an average appropriateness score of 5.3/6.0 ("mostly appropriate" to "completely appropriate"). [10] Our study found that ChatGPT scored best in the infectious disorders section (73.3%), and poorest in the retinal disorders section (50%). Antaki et al showed that the legacy model performed best in general medicine (75%), fundamentals (60%), and cornea (60%), but as well in glaucoma, (37.5%), and pediatrics and strabismus (42.5%), and neuro-ophthalmology (25%), [7] which is in contradiction to Madadi et al findings that showed the potential to diagnose cases related to neuroophthalmology with comparable accuracy to certified neuroophthalmologist, with estimated accuracy of 59% and 82% for ChatGPT 3.5 and ChatGPT 4.0, respectively.…”
Section: Discussionmentioning
confidence: 46%
“…[9] It was also shown that ChatGPT performs accurately when responding to questions about orbital and oculofacial disorders, with an average appropriateness score of 5.3/6.0 ("mostly appropriate" to "completely appropriate"). [10] Our study found that ChatGPT scored best in the infectious disorders section (73.3%), and poorest in the retinal disorders section (50%). Antaki et al showed that the legacy model performed best in general medicine (75%), fundamentals (60%), and cornea (60%), but as well in glaucoma, (37.5%), and pediatrics and strabismus (42.5%), and neuro-ophthalmology (25%), [7] which is in contradiction to Madadi et al findings that showed the potential to diagnose cases related to neuroophthalmology with comparable accuracy to certified neuroophthalmologist, with estimated accuracy of 59% and 82% for ChatGPT 3.5 and ChatGPT 4.0, respectively.…”
Section: Discussionmentioning
confidence: 46%
“…Sarcoidosis is an idiopathic multisystem disorder wherein ocular involvement is seen in approximately 25% of the cases with anterior uveitis being the most common presentation. 1 It can affect any part of the eye including the orbit or lacrimal system with dacryoadenitis being the most common extraocular involvement. The reported incidence of cutaneous involvement in sarcoidosis is 12% to 27% and the incidence of eyelid involvement is even lower.…”
Section: To the Editormentioning
confidence: 99%